Art Exhibition in Digital Art Space as Social Interaction Arena for Artists Towards the Metaverse Era - Ranti Rachmawanti; Cucu Retno Yuningsih (Fakultas Seni Rupa dan Desain ITB, 2022)
With the help of several websites and smartphone application platforms, the number of digital visual arts performances and exhibitions is expanding. This indicates that social relationships have migrated into the virtual realm, offering artists more communication flexibility with a larger audience. This research investigates the social interactionbetween artists and viewers during an art exhibition and performance in a digital art environment. As actual space transforms into virtual space, the creation of digital art space signals a shift in the way art actors and viewers interact with art exhibitions. Digital art spaces allow users to connect and communicate as they see fit in the virtual world. Art exhibitions in the digital art space may be defines as taking place in a 3D environment arena with sophisticated interaction between organizers, artists, and spectators using a variety of communication method.